2014
DOI: 10.1055/s-0034-1386616
|View full text |Cite
|
Sign up to set email alerts
|

Modified Classification and Repair of Perineal Soft Tissue Injuries Associated with Open Pelvic Fractures

Abstract: Perineal soft tissue injuries associated with pelvic fractures can be classified into three types, and the management protocol can be planned according to the classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A study of 29 battlefield trauma patients reported mean blood requirements of 60.3 units during the first 24 h. Ring closure in these patients is often not possible, and other circumstances such as vascular, bowel, genital and bladder injuries are often coexistent[71]. In this context, haemorrhage control, concurrent regional lesions and soft tissue lesion with infection prevention are the main issues to be addressed[72-75]. Apart from clinical inspection, including consideration of possible injuries to the bowel and urinary systems, a contrast CT-scan is mandatory when the patient is haemodynamically stable.…”
Section: Resuscitationmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 29 battlefield trauma patients reported mean blood requirements of 60.3 units during the first 24 h. Ring closure in these patients is often not possible, and other circumstances such as vascular, bowel, genital and bladder injuries are often coexistent[71]. In this context, haemorrhage control, concurrent regional lesions and soft tissue lesion with infection prevention are the main issues to be addressed[72-75]. Apart from clinical inspection, including consideration of possible injuries to the bowel and urinary systems, a contrast CT-scan is mandatory when the patient is haemodynamically stable.…”
Section: Resuscitationmentioning
confidence: 99%
“…Apart from clinical inspection, including consideration of possible injuries to the bowel and urinary systems, a contrast CT-scan is mandatory when the patient is haemodynamically stable. When there is a bowel lesion, early diverting colostomy is usually necessary[72-75]. Experience with battlefield pelvic wounds is often valuable in the subsequent treatment of civilian patients, particularly in relation to open blast injuries to the pelvis[71].…”
Section: Resuscitationmentioning
confidence: 99%